The Effect of Teacher Competency Training on High Order Thinking-Based Learning - Yafie, Evania; Haqqi, Yudha Alfian; Kustiawan, Usep; Astuti, Wuri; Boedi, Donna; Ilhami, Baiq Shofa (Universitas Ahmad Dahlan, 2019)
High order thinking (HOT) -based learning in Early Childhood Education Institution (ECEI) could improve six aspects of preschool-aged children’s development. The preliminary study revealed that the ECE teachers' knowledge of preschool-aged children was low. This surprising phenomenon was caused by teachers' lack of knowledge and minimum training for improving the teachers' competency. Thus, we conducted a study by holding training on the improvement of teacher's competency in HOT-based learning. The present study involved sixty participants comprising Kindergarten and elementary school teachers in Kota Selong, West Nusa Tenggara Province. The present study was aimed at measuring the effect of teacher's competency development training on the improvement of HOT-based learning activities in Kota Selong, East Lombok Regency. The result of the study indicated that the t-count (8.257) > t-table (7.745), meaning that the teacher's competency improvement training significantly affects the improvement of HOTS on both knowledge and implementation of Kindergarten teachers in Kota Selong.